Changes and Correlation between Microbial Communities and Flavor Compounds during the Fermentation Process of Yibin Yacai - Xueling CHEN; Kunyi LIU; Qi WANG; Xinxin NIU; Cheng LIAO; Jiangshan AN; Yunong ZHOU; Zhuo CHEN; Sisi GUAN (Shipin gongye ke-ji)
To investigate the changes and interactions between microbial communities and flavor compounds during the fermentation process of Yibin Yacai, high-throughput sequencing technology and gas chromatography-mass spectrometry were applied to determine the microbial communities and flavor compounds during the fermentation process of Yibin Yacai, while, Spearman correlation was used to explore the relationship between microbial communities and characteristic flavor compounds. The results showed that the dominant microorganisms gradually changed from Pediococcus, Levilactobacillus, Torulaspora and Zygosaccharomyces in the early stage of fermentation to Levilactobacillus, Companilactobacillus, Zygosaccharomyces and Millerozyma. On the 7th month of fermentation, they further changed to Ligilactobacillus, Loigolactobacillus and Zygosaccharomyces, while, Levilactobacillus, Loigolactobacillus, Companilactobacillus, Zygosaccharomyces and Candida became the dominant microorganisms in the later stage of fermentation. Meanwhile, 924 flavor compounds were detected in the fermented samples of Yibin Yacai, among which 33 were characteristic flavor compounds (VIP>1, ROAV>1) during the fermentation process of Yibin Yacai. In addition, Loigolactobacillus, Zygosaccharomyces and Torulaspora were extremely significantly correlated with four terpenoids, including myrcene, 2-methylisoborneol, D-limonene, o-cymene, two phenols, including 4-ethyl-phenol, 4-ethyl-2-methoxy-phenol, and 2-dodecanone, (6Z)-nonen-1-ol, 2-acetyl-3-methylpyrazine, 2-methyl-benzaldehyde (P<0.01). Overall, these findings provide a theoretical basis for utilizing microorganisms to regulate the production and improve fermentation processes of Yibin Yacai.